Faktor-Faktor Yang Berhubungan Dengan Perilaku Skrining Serologi Infeksi Pada Ibu Hamil Di Puskesmas Karang Anyar Kabupaten Lampung Selatan - Marlinda, Marlinda; Kurniasari, Devi; Evayanti, Yulistiana; Utami, Vida Wira (MIDWIFERY JOURNAL, 2024)
The World Healt Organitation (WHO) estimates that as many as 37 million births in the Southeast Asian region each year, while the total maternal and newborn deaths in this region are estimated at 170 and 1.3 million per year. AKI related to pregnancy, childbirth and childbirth was 305 per 100,000 live births. To find out the factors related to the serological screening behavior of maternal infections in pregnant women at the Karang Anyar Health Center in South Lampung Regency in 2019.Type of quantitative research, analytical research design and cross sectional approach. The population of all pregnant women was 42 people and a sample of 42 people with purposive sampling technique. Data collection uses questionnaire sheets and observations and statistical tests used Chi-Square statistical tests.There is a correlation between knowledge and serological screening behavior, obtained p-value (0,000 <α 0,05). OR: 19.00. There is a relationship between attitude and serological screening behavior, obtained p-value (0.006 <α 0.05). OR: 7,933. There is a relationship between health worker support and serological screening behavior, obtained by p-value (0,000 <α 0,05). OR: 30,600.There is a relationship between knowledge, attitudes and support of health workers by serological screening of maternal infections. It is necessary for pregnant women to increase their knowledge so that they understand more about the knowledge of the dangers of infection in mothers by routinely appreciating health education activities carried out by health workers. Keywords : Behavior Screening Maternal Infection, Knowledge, Attitude, Health Officer Support ABSTRAK World Healt Organitation (WHO) memperkirakan, sebanyak 37 juta kelahiran dikawasan Asia Tenggara setiap tahun, sementara total kematian ibu dan bayi baru lahir dikawasan ini diperkirakan 170 dan 1,3 juta pertahun. AKI yang berkaitan dengan kehamilan, persalinan, dan nifas sebesar 305 per 100.000 kelahiran hidup. Tujuan penelitian ini adalah diketahui faktor-faktor yang berhubungan dengan perilaku skrining serologi infeksi maternal pada ibu hamil di Puskesmas Karang Anyar Kabupaten Lampung Selatan Tahun 2019.Jenis penelitian kuantitatif, rancangan penelitian analitik dan pendekatan  cross sectional. Populasi seluruh ibu hamil sebanyak 42 orang dan sampel sebanyak 42 orang dengan teknik purposive sampling. Pengumpulan data menggunakan lembar kuesioner dan observasi dan Uji statistik yang digunakan uji statistik Chi-Square.Ada hubungan pengetahuan dengan perilaku skrining serologi, diperoleh p- value (0,000 <α 0,05). OR: 19,00. Ada hubungan sikap dengan perilaku skrining serologi, diperoleh p-value (0,006 <α 0,05). OR: 7,933. Ada hubungan dukungan petugas kesehatan dengan perilaku skrining serologi, diperoleh p-value (0,000 <α 0,05). OR: 30,600. Ada hubungan pengetahuan, sikap dan dukungan petugas kesehatan dengan perilaku skrining serologi infeksi maternal. Disarankan ibu hamil meningkatkan pengetahuan agar lebih mengetahui tentang pengetahuan akan bahaya infeksi maternal pada kehamilan dengan cara rutin berpartisipasi dalam kegiatan penyuluhan atau pendidikan kesehatan yang dilakukan petugas kesehatan. Kata Kunci : Perilaku Skrining Serologi Infeksi Maternal, Pengetahuan, Sikap, Dukungan Petugas Kesehatan